Analysis of Work Posture Based on Quick Exposure Check & Manual Task Risk Assessment Method - Kristiana, Stefani Prima Dias; Tania, Fransisca (Sekolah Tinggi Teknologi Adisutjipto, 2019)
Manual material handling (MMH) is one of the most vulnerable forms of activity with the emergence of risk of injury to the body, for example musculoskeletal disorders (MSDs). This study aims to analyze the work posture carried out by workers at PT. Multitech Advanced Printing Indonesia on the work of moving raw materials. The work includes a series of activities, namely lifting, carrying, and lowering. Of the three activities, lowering was chosen as the most potentially dangerous for workers. This study uses the Quick Exposure Check (QEC) method and Manual Task Risk Assessment (ManTRA) to assess the risk of work injury. Based on the results of the QEC method, the value obtained is 59.88% while the ManTRA method gives the highest value of 2 points from the three conditions for the improvement work posture. Both methods assess work posture as dangerous becauses of the bending position of the back